Pengaruh Promosi Media Sosial, Word of Mouth dan Reference Group Terhadap Keputusan Pembelian Maxmil CV. Indo Jaya Putra - Shania Kwok, Catherine; Agustina K, Tin; Pradiani, Theresia (PUBLICNESS: Journal of Public Administration Studies, 2025)
The purpose of this study was to determine whether there is an influence of social media promotion, word of mouth and reference groups on the purchasing decision of Maxmil at CV. Indo Jaya Putra both partially and simultaneously. The population used is customers with product purchases at CV. Indo Jaya Putra with the following criteria: Customers follow one of the Maxmil CV. Indo Jaya Putra social media accounts, Customers who have participated in the Maxmil CV. Indo Jaya Putra product demo in the East Java area, and Customers who are members of the East Java area UMKM group. The sample used was 100 customers with Saturated or census sampling. The results of this study are that the variables of promotion on social media, WOM, and reference groups have a partial and simultaneous effect on the purchasing decision of Maxmil CV. Indo Jaya Putra.